Réponses

  • Utilisateur Brainly
2014-09-06T16:56:15+02:00
Factoriser :

f(x) = (3x - 1)² - 36
      = (3x - 1)² - 6²     identité remarquable : (a + b)(a - b) = a² - b²
      = (3x - 1 + 6)(3x - 1 - 6)
      = (3x + 5)(3x - 7)
merci. il me demande avant développer et réduire. est ce que je dois utiliser l'expression réduite pour factoriser ?
2014-09-06T16:58:13+02:00
Bonjour

f(x) = (3x - 1)² - 36
f(x) = [(3x-1) + 6][(3x-1)-6]
f(x) = (3x-1 + 6)(3x-1-6)
f(x) = (3x+5)(3x-7)
merci! il me demande avant de développer et réduire. est ce que je dois utiliser l'expression réduite pour factoriser ?